Twitter Diplomacy @Kemlu_RI: A Case Study of Bali Democracy Forum 2019 - Ludiro Madu (Jurnal Hubungan Internasional, 2021)
Following the increasing use of social media, particularly Twitter, the Indonesian MOFA made an official Twitter account @Kemlu_RI for disseminating information. The paper aims to to analyse the trend of tweeting at the official Twitter account of the Indonesian Ministry of Foreign Affairs (MOFA), @Kemlu_RI. This research used a qualitative approach through online media, Twitter. Data was obtained through observation of the conversation trend on Twitter by monitoring @Kemlu_RI account. This research focussed on the use of hashtag #BDF2019. Using ‘Drone Emprit Academic’ (DEA), this research collected data on five days of Twitter conversation. The DEA analysis resulted in 1.088 conversations. Rather than only disseminating information, the use of DEA for analysing #BDF2019 at @Kemlu_RI turned out to produce more findings. The result of this study shows that the DEA usage gives more benefits to Indonesian digital diplomacy, such as top hashtag, top influencer, social network analyses, and most engaged users, rather than just general dissemination of information of the BDF 2019. Therefore, the use of the DEA is very significant for resulting in more accurate data for Indonesian MOFA in order to manage a better strategy for using Twitter in its future diplomatic agenda.